Information sources for the virtual audience about the Uyghur crisis and its impact on public opinion regarding China’s policy are analyzed through An analytical study of the Arabic China News page on Twitter - Saad, Hussein Abdalla (Journal of Humanities & Social Sciences, 2023)
The study aimed to focus on the sources of information for the virtual public regarding the Uighur crisis and its impact on public opinion about China’s policies. It sought to identify the topics discussed in virtual public comments. The study falls within the descriptive research category and adopts an analytical approach. It relied on the analysis of comments from the virtual audience on the main question concerning the sources of information that the public relies on regarding the Chinese authorities’ treatment of Muslims in general and the Uighurs in particular. The analysis was conducted on the Arabic-language China News page on Twitter in July 2022, which included a total of 607 comments. The most important results of the study were that Twitter ranked first at 20.2% as the source of information relied upon by the virtual public, while news websites ranked last at 2%. The results indicated that "killings in various methods" ranked first at 26.6% as the most prominent topics raised by the virtual public in their comments on the Uighur issue, while issues related to "sexual violence" ranked last at 5.6%. The study’s findings revealed that video content ranked first at 34% as the most prominent highlighting element in the virtual public’s comments about the Uighur Muslims, while electronic links ranked last at 1.4%. The results also highlighted that the Arabic language ranked first at 49.6%, while the Chinese language ranked last at 9%.